Deadly embrace - Riedel, Bruce (New Delhi, 2011)
Pakistan and the United States have been locked in a deadly embrace for decades. Successive American presidents from both parties have pursued narrow short-term interests in the South Asian nation, and many of the resulting policies proved counterproductive in the long term, contributing to political instability and a radicalized public. This background has helped set the stage for the global jihad confronting much of the world today. In Deadly Embrace, Bruce Riedel explores the forces behind these developments, explaining how and why the history of Pakistan-U.S. relations has unfolded as it has. He explains what the United States can do now to repair the damage and how it can avoid making similar mistakes in dealing with extremist forces in Pakistan and beyond.
Keywords: Pakistan-United States-Foreign relations